Case report: the use of the AWIN welfare assessment protocol to monitor a group of abandoned donkeys - Farias, Sharacely de Souza; Gameiro, Mariana Bombo Perozzi; Montechese, Ana Carolina Dierings; Bernardino, Thiago; Oliveira, Chiara Albano de Araujo; Zanella, Adroaldo José (Brazilian Journal of Veterinary Research and Animal Science, 2021)
The objective of this study was to reach a diagnosis of the living conditions of abandoned donkeys kept in a restricted farm area through the assessment of their welfare level utilizing the AWIN protocol as a methodological tool. These animals were supposed to be sent to slaughter, but after the activity was temporarily banned, they were abandoned by traders. The protocol of welfare assessment was associated with general environmental and sanitary conditions. Information regarding the mortality rates was also gathered. According to the welfare assessment results, the living conditions of these animals were acceptable in some areas, despite the insufficient shade and shelter, a 3-month food restriction period, and a mortality rate of over 70%. These results demonstrate that welfare assessment protocols must be adapted to crises and databases for welfare indicators in diverse conditions must be created.